Social and cultural backgrounds of terrorism in the modern sociocultural situation of the world community - Rashid Musaidinovich Makhmudov (Вестник Майкопского государственного технологического университета, 2023)
The article examines the socio-cultural preconditions of terrorism in the world history of the 20th century. The current situation in the Russian Federation indicates the need to create an effective organizational and legal mechanism for countering terrorism, which infringes on the rights, freedoms and legitimate interests of the population of the Russian Federation and its state sovereignty. The provisions have been stated that determine the importance of studying the phenomenon of terrorism in the context of the growth of globalization processes and active opposition to them on the part of opponents of globalization. The author emphasizes the idea that deepening of the modern spiritual crisis influences the replacement of traditional moral values with a pragmatic orientation towards personal material success, which greatly contributes to the development of international terrorism. Despite a fairly wide list of subjects empowered by the national legislation of the Russian Federation to fight terrorism, the current legal field has not developed a concept that defines terrorism not only as a form of illegal action, but as a socio-cultural problem. In many respects, this became one of the reasons for the lack of interaction and coordination between the executive authorities and management in terms of its organization and implementation of measures aimed at countering terrorist manifestations. The study concludes that victory in the fight against terrorism cannot be achieved solely by forceful methods and state institutions. Civil society must make its contribution to the fight against terrorism.